Double trouble (McArdle's disease and myasthenia gravis): How can exercise help? - Lucia, Alejandro; Maté-Muñoz, José L.; Pérez, Margarita; Foster, Carl; Gutiérrez-Rivas, Eduardo; Arenas, Joaquín (Muscle & nerve, 2007)
We report a 29‐year‐old patient with McArdle's disease and myasthenia gravis. She had been debilitated with McArdle's disease since childhood (with marked rhabdomyolysis) and was obese. Myasthenia gravis was diagnosed at 24 years of age. After 3 months of aerobic exercise training, her exercise capacity increased significantly and she regained the ability to live independently. We conclude that even patients with profound neuromuscular diseases may benefit from carefully prescribed exercise training. Muscle Nerve, 2006